365 Panchatantra stories. (Om kidz books international)
The stories of panchatantra are ancient indian fables that were written in sanskrit and pali. the central characters in these fascinating fables are mainly animals and birds. they show their typical characteristics in these stories and impart valuable life-lessons and morals. this beautifully illustrated book offers a classic panchatantra tale for every day of the year. Read about clever hares, cunning jackals, evil hunters, great friends and more! 365 panchatantra stories is the perfect addition to a child's library